Child care and training - Faegre, Marion L.; Anderson, John E. ;Harris, Dale B. (Minneapolis, Minnesota : University of Minnesota Press, 1958)
This book has had a long and successful history, attested by its many edition and printing. In Preparing a revision after the ten years passed since the seventh edition, we have looked closely at current concepts of personality and growth.
1. The Young child -- 2. How children grow -- 3. General care, including diet and clothing -- 4. children's diseases and accidents -- 5. The Development of behavior -- 6. How children learn -- 7. Eliminative and other early habits -- 8. Learning to enjoy meals and mealtime -- 9. Learning to rest well -- 10. Emotional behavior -- 11. Constructive discipline -- 12. Curiosity, questioning, and sex education -- 13. Imagination, truth, and falsehood -- 14. Play -- 15. Social development -- 16. Personality, adjustment, and mental health -- 17. Books and reading -- 18. The Family.
Includes bibliographical references and index.
Keywords: CHILD CARE